Starting 2018 with a bang

Calculus Level 5

k = 0 ( 2018 3 k ) = a b + c d \large \sum_{k=0}^{\infty} \binom{2018}{3k} = \frac {a^b+c}d

The equation above holds true for some nonzero integers a a , b b , c c and d d with a a and d d being primes. Find a + b + c + d a+b+c +d .

Notation: ( M N ) = M ! N ! ( M N ) ! \dbinom MN = \dfrac {M!}{N! (M-N)!} denotes the binomial coefficient .


The answer is 2022.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jan 14, 2018

By binomial theorem , we have ( 1 + x ) n = k = 0 n ( n r ) x r \displaystyle (1+x)^n = \sum_{k=0}^n \binom nr x^r . Since ( n r ) x r = 0 \displaystyle \binom nr x^r = 0 if r > n r > n , then k = 0 ( n r ) x r = k = 0 n ( n r ) x r \displaystyle \sum_{k=0}^\infty \binom nr x^r = \sum_{k=0}^n \binom nr x^r . Now, let us consider when x = 1 , ω , ω 2 x = 1, \omega, \omega^2 , where ω \omega is the complex cube root of unit.

( 1 + 1 ) 2018 = ( 2018 0 ) 1 + ( 2018 1 ) 1 + ( 2018 2 ) 1 + ( 2018 3 ) 1 + ( 2018 4 ) 1 + ( 2018 5 ) 1 + ( 2018 6 ) 1 + + ( 2018 2018 ) 1 ( 1 + ω ) 2018 = ( 2018 0 ) 1 + ( 2018 1 ) ω + ( 2018 2 ) ω 2 + ( 2018 3 ) 1 + ( 2018 4 ) ω + ( 2018 5 ) ω 2 + ( 2018 6 ) 1 + + ( 2018 2018 ) ω 2 Note that ω 3 = 1 ( 1 + ω 2 ) 2018 = ( 2018 0 ) 1 + ( 2018 1 ) ω 2 + ( 2018 2 ) ω + ( 2018 3 ) 1 + ( 2018 4 ) ω 2 + ( 2018 5 ) ω + ( 2018 6 ) 1 + + ( 2018 2018 ) ω \begin{aligned} (1+1)^{2018} & = \binom {2018}0 \cdot 1 + \binom {2018}1 \cdot 1 + \binom {2018}2 \cdot 1 + \binom {2018}3 \cdot 1 + \binom {2018}4 \cdot 1 + \binom {2018}5 \cdot 1 + \binom {2018}6 \cdot 1 + \cdots + \binom {2018}{2018} \cdot 1 \\ (1+\omega)^{2018} & = \binom {2018}0 \cdot 1 + \binom {2018}1 \omega + \binom {2018}2 \omega^2 + \binom {2018}3 \cdot 1 + \binom {2018}4 \omega + \binom {2018}5 \omega^2 + \binom {2018}6 \cdot 1 + \cdots + \binom {2018}{2018} \omega^2 & \small \color{#3D99F6} \text{Note that }\omega^3 = 1 \\ (1+\omega^2)^{2018} & = \binom {2018}0 \cdot 1 + \binom {2018}1 \omega^2 + \binom {2018}2 \omega + \binom {2018}3 \cdot 1 + \binom {2018}4 \omega^2 + \binom {2018}5 \omega + \binom {2018}6 \cdot 1 + \cdots + \binom {2018}{2018} \omega \end{aligned}

( 1 + 1 ) 2018 + ( 1 + ω ) 2018 + ( 1 + ω 2 ) 2018 = 3 ( 2018 0 ) + 3 ( 2018 3 ) + 3 ( 2018 6 ) + 3 ( 2018 9 ) + + 3 ( 2018 2016 ) Note that 1 + ω + ω 2 = 0 \begin{aligned} \implies (1+1)^{2018} + (1+\omega)^{2018} + (1+\omega^2)^{2018} & = 3 \binom {2018}0 + 3\binom {2018}3 + 3\binom {2018}6 + 3 \binom {2018}9 + \cdots + 3 \binom {2018}{2016} & \small \color{#3D99F6} \text{Note that }1+ \omega + \omega^2 = 0 \end{aligned}

k = 0 n ( 2018 3 k ) = ( 1 + 1 ) 2018 + ( 1 + ω ) 2018 + ( 1 + ω 2 ) 2018 3 Note that 1 + ω + ω 2 = 0 = 2 2018 + ( ω 2 ) 2018 + ( ω ) 2018 3 Note that ω 3 = 1 = 2 2018 + ω + ω 2 3 = 2 2018 1 3 \begin{aligned} \implies \sum_{k=0}^n \binom {2018}{3k} & = \frac {(1+1)^{2018} + (1+\omega)^{2018} + (1+\omega^2)^{2018}}3 & \small \color{#3D99F6} \text{Note that }1+ \omega + \omega^2 = 0 \\ & = \frac {2^{2018} + (-\omega^2)^{2018} + (-\omega)^{2018}}3 & \small \color{#3D99F6} \text{Note that }\omega^3 = 1 \\ & = \frac {2^{2018} + \omega + \omega^2}3 \\ & = \frac {2^{2018} -1}3 \end{aligned}

Therefore, a + b + c + d = 2 + 2018 1 + 3 = 2022 a+b+c+d = 2+2018-1+3 = \boxed{2022} .

Efren Medallo
Jan 12, 2018

We will attempt to use the concept of Fourier transforms in this problem.

First off, we will use the fact that

k = 0 ( n k ) x k = ( x + 1 ) n \large\displaystyle\sum_{k=0}^{\infty} \binom{n}{k}x^k = (x+1)^n

Since we want to only consider every 3rd element of this general summation, we look for ways to generate such summations which will cancel the other elements. So we will look for values of x x which will eliminate the unwanted elements.

If we take a look at the "weights" of the elements of the sequence which are considered, it looks like

( 1 , 0 , 0 , 1 , 0 , 0... ) (1, 0, 0, 1, 0, 0 ... )

Which means that this sequence repeats periodically every 3 elements. This is the weight sequence that we desire.

On the general equation, since all elements are considered, the weight sequence is

( 1 , 1 , 1 , 1 , 1... ) (1, 1, 1, 1, 1... )

Now, what are sequences which are powers of a single number which are of period 3? The simplest answer is the solution set to x 3 = 1 x^3 = 1 , one of which is the one shown above.

The other two are as follows:

( 1 , e 2 i π 3 , e 2 i π 3 . . . ) ( 1, e^{\frac{2i \pi}{3}}, e^{-\frac{2i \pi}{3}} ...)

( 1 , e 2 i π 3 , e 2 i π 3 . . . ) ( 1, e^{-\frac{2i \pi}{3}}, e^{\frac{2i \pi}{3}} ...)

Now we can construct the weight sequence we want!

3 ( 1 , 0 , 0 , 1... ) = ( 1 , 1 , 1... ) + ( 1 , e 2 i π 3 , e 2 i π 3 . . . ) + ( 1 , e 2 i π 3 , e 2 i π 3 . . . ) 3 (1,0,0,1...) = (1,1,1...) + ( 1, e^{\frac{2i \pi}{3}}, e^{-\frac{2i \pi}{3}} ...) + (1, e^{-\frac{2i \pi}{3}}, e^{\frac{2i \pi}{3}} ...)

(See what I did there?)

Translating these back to the summations, we get

3 k = 0 ( n 3 k ) = ( 1 + 1 ) n + ( 1 + e 2 i π 3 ) n + ( 1 + e 2 i π 3 ) n 3 \large\displaystyle\sum_{k=0}^{\infty} \binom{n}{3k} = (1+1)^n + (1 + e^{\frac{2i \pi}{3}})^n + ( 1 +e^{-\frac{2i \pi}{3}})^n

3 N = 2 n + ( 1 + e 2 i π 3 ) n + ( 1 + e 2 i π 3 ) n 3N = 2^n + (1 + e^{\frac{2i \pi}{3}})^n + ( 1 +e^{-\frac{2i \pi}{3}})^n

Now, we express

e 2 i π 3 = 1 2 + i 3 2 e^{\frac{2i \pi}{3}} = - \frac{1}{2} + i \frac{\sqrt{3}}{2}

and

e 2 i π 3 = 1 2 i 3 2 e^{-\frac{2i \pi}{3}} = - \frac{1}{2} - i \frac{\sqrt{3}}{2}

This simplifies it down to

3 N = 2 n + ( 1 1 2 + i 3 2 ) n + ( 1 + 1 2 i 3 2 ) n 3N = 2^n + (1 - \frac{1}{2} + i \frac{\sqrt{3}}{2})^n + ( 1 + - \frac{1}{2} - i \frac{\sqrt{3}}{2} )^n

3 N = 2 n + ( 1 2 + i 3 2 ) n + ( 1 2 i 3 2 ) n 3N = 2^n + ( \frac{1}{2} + i \frac{\sqrt{3}}{2})^n + ( \frac{1}{2} - i \frac{\sqrt{3}}{2} )^n

3 N = 2 n + ( e 2 i π 3 ) n + ( e 2 i π 3 ) n 3N = 2^n + (- e^{-\frac{2i \pi}{3}})^n + ( -e^{\frac{2i \pi}{3}})^n

3 N = 2 n + ( 1 ) n [ e 2 i π n 3 + e 2 i π n 3 ] 3N = 2^n + (-1)^n [ e^{ \frac{2 i \pi n}{3}} + e^{\frac{-2i \pi n}{3}} ]

3 N = 2 n + ( 1 ) n ( 2 cos 2 π n 3 ) 3N = 2^n + (-1)^n (2 \cos{ \frac{2\pi n}{3}})

3 N = 2 n + 2 ( 1 ) n ( cos 2 π n 3 ) 3N = 2^n + 2(-1)^n ( \cos{ \frac{2\pi n}{3}})

N = 2 3 [ 2 n 1 + ( 1 ) n ( cos 2 π n 3 ) ] N = \frac {2}{3} [ 2^{n-1} + (-1)^{n}( \cos{ \frac{2\pi n }{3}})]

Plugging in n = 2018 n =2018 gives us

N = 2 3 [ 2 2017 + ( 1 ) 2018 ( cos 4036 π 3 ) ] N = \frac {2 }{3} [ 2^{2017} + (-1)^{2018}( \cos{ \frac{4036\pi }{3}})]

N = 2 2018 1 3 \large\boxed{N = \frac{2^{2018} -1}{3}}

Hey, try this .

Akshat Sharda - 3 years, 4 months ago

Log in to reply

Indeed, I have to say it took me a while to figure out what to do with it. Hahaha

Efren Medallo - 3 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...